How Music Works - Byrne, David 1952- (San Francisco, CA McSweeney's, 2012)
How Music Works is David Byrnes remarkable and buoyant celebration of a subject he has spent a lifetime thinking about. In it he explores how profoundly music is shaped by its time and place, and he explains how the advent of recording technology in the twentieth century forever changed our relationship to playing, performing, and listening to music.Acting as historian and anthropologist, raconteur and social scientist, he searches for patternsand shows how those patterns have affected his own work over the years with Talking Heads and his many collaborators, from Brian Eno to Caetano Veloso. Byrne sees music as part of a larger, almost Darwinian pattern of adaptations and responses to its cultural and physical context. His range is panoptic, taking us from Wagnerian opera houses to African villages, from his earliest high school reel-to-reel recordings to his latest work in a home music studio (and all the big studios in between).Touching on the joy, the physics, and even the business of making music, How Music Works is a brainy, irresistible adventure and an impassioned argument about musics liberating, life-affirming power.
Keywords: 21st Century (2001-2100); Music theory; Music philosophy and esthetics; Popular music; Singer; Biography